Knowledge on Lenggong place attractions: Perspectives from local communities - Hassan, Fatimah; Che Dah, Farhana (2013)
Level of knowledge on place attractions by local community is crucial in transforming and promoting a destination as tourist attractions. The purpose of this study is to find out the level of knowledge and perceptions on Lenggong Valleys’ place attributes and attractions from local communities. Lenggong Valley which has unique and outstanding archeogeological and heritage products, has been declared as a world heritage site on 30th June 2012 by UNESCO, a worldwide organization for educational, scientific, and culture. Unfortunately, the finding of a survey on 500 residences in Lenggong Valley area shows that, the knowledge of the locals on Lenggong place attractions is low. About 67.8% did not know the Toba volcanic ash in Bukit Sapi and 65.6% never knew the existing of Bukit Bunuh, an area with exposed impactites since Middle-Early Pleistocene. Since their understanding is less inclusive, this paper will suggest several activities such as heritage fair, site tour and mobile exhibition for further actions by destination manager. It is the intention of this paper to bring to discussion these issues as part of strategies to develop and improve Lenggong’s competitive advantages as one of the world’s popular tourism destinations in the future.